2016
DOI: 10.1177/0170840616634131
|View full text |Cite
|
Sign up to set email alerts
|

The Network Firm as a Political Coalition

Abstract: The article uses a qualitative case study of fifteen years in the production network that revolves about Fiat Auto to depict the “network firm” as a political coalition. It used a discussion of radical outsourcing of production in the 1990s, a short-lived and ill-fated alliance with General Motors in 2001, a descent to the brink of bankruptcy in 2004, a return to profitability by 2007, and, finally, the sudden acquisition of control of Chrysler in 2009 to reconstruct James March’s classic Carnegie model of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 69 publications
1
24
0
Order By: Relevance
“…coercion. These two papers, by Whitford and Zirpoli (2016) and Dörrenbächer and Gammelgaard (2016), have the closest links with current debates in IB research. The first paper focuses on MNCs as network firms with fragmented power structures that are conceptualized as 'bundles of coalitions'.…”
Section: Different Faces Of Power In Mncs: Key Ideas and Findings In mentioning
confidence: 94%
“…coercion. These two papers, by Whitford and Zirpoli (2016) and Dörrenbächer and Gammelgaard (2016), have the closest links with current debates in IB research. The first paper focuses on MNCs as network firms with fragmented power structures that are conceptualized as 'bundles of coalitions'.…”
Section: Different Faces Of Power In Mncs: Key Ideas and Findings In mentioning
confidence: 94%
“…Framing organizations as fragmented entities, organizational politics scholars (e.g., Glynn, 2000;Monin et al, 2013;Whitford & Zirpoli, 2016) highlight that different organizational actors can rely on different belief systems and practices to provide meaning to their social reality. This situation, where different belief systems and practices co-exist, is described as a situation of competing logics (Pache & Santos, 2010).…”
Section: Competing Partnership Logicsmentioning
confidence: 99%
“…However, we acknowledge that coalition building can also span organizational boundaries. For instance, studying the history of the automotive company Fiat, Whitford and Zirpoli (2016) describe how coalition building between engineers of Fiat and engineers of its suppliers impacted important insourcing and outsourcing decisions. Exploring such coalition-building across organizational boundaries may not only be relevant in dyadic inter-organizational contexts, but can also help to move forward our understanding of even more complex collaborative phenomena, such as multiparty constellations and innovation ecosystems.…”
Section: Political Perspective On Inter-organizational Relationships:mentioning
confidence: 99%
“…The Italian automotive industry is characterized by a significant fragmentation of the supply system in a plethora of small and medium size firms, highly specialized on small phases of the production process, and with very different attitudes towards innovation activities. Integrating knowledge for innovation purposes is then one of the more problematic challenges of the Italian automotive supplier network, pushed by the industry evolution towards the development of a complex and articulated network of inter-organizational relationships (see for an overview Whitford and Zirpoli, 2016, Enrietti and Whitford, 2005, Zirpoli and Caputo, 2002. In the last decade, in fact, the national carmaker (Fiat now Fiat Chrysler Automobiles), whose production choices deeply affected all small and medium suppliers, decided to reduce dramatically internal production levels 2 .…”
Section: The Setting: the Italian Automotive Industrymentioning
confidence: 99%
“…Conversely, it has been showed that the governance toolkit (Whitford & Zirpoli, 2016), innovation competences, and relative bargaining position (Robertson & Langlois, 1995) might influence the governance of vertical relationships. Notably, in vertical supply chains firms occupying different tiers have often very different characteristics.…”
Section: Introductionmentioning
confidence: 99%